National Education Strategy in Facing the Flow of Cosmopolitanism - Oktavia Rumengan; R. Madhakomala; Linda Ika Mayasari (Eastasouth Institute, 2026)
The current of cosmopolitanism as a consequence of globalization has brought significant changes to the national education system in Indonesia. This phenomenon is characterized by increased cultural exchange, the development of digital technology, global mobility, and the penetration of universal values that influence the orientation of national education. On the one hand, cosmopolitanism opens opportunities for increasing global competence, transforming learning, and strengthening the competitiveness of human resources. However, on the other hand, this current also presents challenges in the form of a weakening of national identity, a character crisis of the younger generation, the commercialization of education, and disparities in access to educational technology. This study aims to analyze the national education strategy in dealing with the current of cosmopolitanism and identify the challenges facing Indonesian education in the global era. The study uses a qualitative approach with a literature study method through analysis of scientific journals, education policy documents, academic books, and reports from national and international institutions. The results show that the national education strategy needs to be directed at strengthening Pancasila-based character education, revitalizing local culture, developing global competence, inclusive digital transformation of education, and increasing teacher capacity. This study emphasizes that national education must be able to build a balance between global openness and strengthening national identity so that Indonesia can adapt to a global society without losing its identity.